Habituação das respostas cardiovasculares ao estresse de restrição em ratos - Benini, Ricardo (2019)
Habituation refers to any decrease in physiological and behavioral responsiveness to a repeated stimulus, while sensitization is a hyperresponsiveness trigger by the same stimulus or other stimuli. Although the habituation of neuroendocrine responses to stress is well described in the literature, a progressive reduction of cardiovascular responses during repeated exposure to the same aversive stimulus is still controversial. Therefore, in the present study we have tested the hypothesis that cardiovascular responses habituate during repeated exposure to restraint stress in rats, and this effect is influenced by the length, frequency and number of aversive sessions; exposure to other stressors and physical training; as well as the sex, age and lineage of the animals. The habituation of corticosterone response to repeated restraint stress was also evaluated. We observed that serum corticosterone increase was decreased during stress and the recovery period of the 10th restraint session when compared to the response during an acute session. Regarding cardiovascular responses, a faster heart rate (HR) return was observed at baseline during the post-stress period of the 10th 60-min restraint stress session in male and female adult Wistar rats, in elderly Wistar rats, and in Holztman adult rats. Daily 120-minute sessions decreased blood pressure and HR values during the recovery of the 10th session in adult Wistar rats. Adolescent Wistar rats presented a reduction in HR response during the 10th restraint session. Spontaneously hypertensive rats (SHR) and Long-Evans did not show any sign of habituation of cardiovascular responses to restraint stress. Regarding the frequency, tachycardia during the 10th session was increased in adult Wistar rats submitted to 60 minutes of restraint presented on alternate days, and decreased in rats submitted to the protocol of 5 daily sessions followed by 2 days of rest. Exposure to other chronic stressors including chronic varied stress and social isolation stress as well as a treadmill physical training protocol inhibited the process of habituation of the HR response observed during the 10th session of 60 minutes of restraint stress. The chronic varied stress and social isolation also facilitated the responses of, respectively, blood pressure and HR to restraint stress. These results provide evidence of habituation of cardiovascular responses after repeated exposure to restraint stress, and this effect is dependent on duration, frequency and number of exposures; besides being influenced by the sex, period of the life and lineage of the animals. The habituation process was also inhibited by exposure to other chronic stressors and by physical training.